A juxtaposed review on adsorptive removal of PFAS by metal-organic frameworks (MOFs) with carbon-based materials, ion exchange resins, and polymer adsorbents. (January 2023) - Karbassiyazdi, Elika; Kasula, Medha; Modak, Sweta; Pala, Jasneet; Kalantari, Mohammad; Altaee, Ali; Esfahani, Milad Rabbani; Razmjou, Amir
Abstract: The removal of poly- and perfluoroalkyl substances (PFAS) from the aquatic environment is a universal concern due to the adverse effects of these substances on both the environment and public health. Different adsorbents, including carbon-based materials, ion exchange resins, biomaterials, and polymers, have been used for the removal of short-chain (C < 6) and long-chain (C > 7) PFAS from water with varying performance. Metal-organic frameworks (MOFs), as a new generation of adsorbents, have also been recently used to remove PFAS from water. MOFs provide unique properties such as significantly enhanced surface area, structural tunability, and improved selectivity compared to conventional adsorbents. However, due to various types of MOFs, their complex chemistry and morphology, different PFAS compounds, lack of standard adsorption test, and different testing conditions, there are inconclusive and contradictory findings in the literature. Therefore, this review aims to provide critical analysis of the performance of different types of MOFs in the removal of long-chain (C > 7), short-chain (C < 6), and ultra-short-chain (C < 3) PFAS and comprehensively study the efficiency of MOFs for PFAS removal in comparison with other adsorbents. In addition, the adsorption mechanisms and kinetics of PFAS components on different MOFs, including Materials of Institute Lavoisier (MIL), Universiteit of Oslo (UiO), Zeolitic imidazolate frameworks (ZIFs), Hong Kong University of Science and Technology (HKUST), and other hybrid types of MOF were discussed. The study also discussed the effect of environmental factors such as pH and ionic strength on the adsorption of PFAS on MOFs. In addition to the adsorption process, the reusability and regeneration of MOFs in the PFAS removal process are discussed. Finally, challenges and future outlooks of the utility of MOFs for PFAS removal were discussed to inspire future critical research efforts in removing PFAS. Graphical abstract: Image 1 Highlights: PFAS (per- and poly-fluoroalkyl substances) contaminants have serious health and environment implications. PFAS is almost non-degradable in nature is remediation is very challenging and expensive. Metal-organic frameworks (MOF) has been emerging as a new class of PFAS adsorbents. This work critically reviews recent advances in the application MOFs for PFAS removal.